MOTHER'S KNOWLEDGE ABOUT INTEGRATED HEALTHCARE CENTER WITH TODDLERS' VISITS AT INTEGRATED HEALTHCARE CENTER - Nurhidayah .; Suhartini -; Jajuk Winarni; Neta Ayu Andera (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2023)
Integrated healthcare center (Posyandu) is an important health service for babies and toddlers at the earliest, visits by toddlers at the posyandu are related to the role of the mother as the person most responsible for the health of her toddler. Visits by mothers of toddlers are influenced by education, employment status, income level, level of knowledge, age of toddlers, and number of toddlers. This research aimed to determine the relationship between the knowledge of mothers of toddlers about posyandu activities and visits by toddlers in North Tanon Hamlet, Tanon Village, Papar District. The research design used correlation analysis with a cross-sectional approach. The sample in this study was 44 respondents taken using a purposive sampling technique. Data collection uses a questionnaire. Data were analyzed using the Spearman Rho Test. The research results showed that most respondents had insufficient knowledge, as many as 27 respondents (61.4%), and most respondents made inactive visits as many as 21 respondents (47.7%). The analysis showed a significant relationship between maternal knowledge and toddler visits at Posyandu (p-value = 0.003; Î± <0.05). Mothers' knowledge about Posyandu and the benefits of Posyandu can influence mothers' motivation to bring their toddlers to Posyandu visits. Mothers with poor knowledge about Posyandu can reduce toddlers' visits to Posyandu.